Solve for x, y
Tick mark Image
Graph

Similar Problems from Web Search

Share

x-3-y=0
Consider the first equation. Subtract y from both sides.
x-y=3
Add 3 to both sides. Anything plus zero gives itself.
37-3x-y=0
Consider the second equation. Subtract y from both sides.
-3x-y=-37
Subtract 37 from both sides. Anything subtracted from zero gives its negation.
x-y=3,-3x-y=-37
To solve a pair of equations using substitution, first solve one of the equations for one of the variables. Then substitute the result for that variable in the other equation.
x-y=3
Choose one of the equations and solve it for x by isolating x on the left hand side of the equal sign.
x=y+3
Add y to both sides of the equation.
-3\left(y+3\right)-y=-37
Substitute y+3 for x in the other equation, -3x-y=-37.
-3y-9-y=-37
Multiply -3 times y+3.
-4y-9=-37
Add -3y to -y.
-4y=-28
Add 9 to both sides of the equation.
y=7
Divide both sides by -4.
x=7+3
Substitute 7 for y in x=y+3. Because the resulting equation contains only one variable, you can solve for x directly.
x=10
Add 3 to 7.
x=10,y=7
The system is now solved.
x-3-y=0
Consider the first equation. Subtract y from both sides.
x-y=3
Add 3 to both sides. Anything plus zero gives itself.
37-3x-y=0
Consider the second equation. Subtract y from both sides.
-3x-y=-37
Subtract 37 from both sides. Anything subtracted from zero gives its negation.
x-y=3,-3x-y=-37
Put the equations in standard form and then use matrices to solve the system of equations.
\left(\begin{matrix}1&-1\\-3&-1\end{matrix}\right)\left(\begin{matrix}x\\y\end{matrix}\right)=\left(\begin{matrix}3\\-37\end{matrix}\right)
Write the equations in matrix form.
inverse(\left(\begin{matrix}1&-1\\-3&-1\end{matrix}\right))\left(\begin{matrix}1&-1\\-3&-1\end{matrix}\right)\left(\begin{matrix}x\\y\end{matrix}\right)=inverse(\left(\begin{matrix}1&-1\\-3&-1\end{matrix}\right))\left(\begin{matrix}3\\-37\end{matrix}\right)
Left multiply the equation by the inverse matrix of \left(\begin{matrix}1&-1\\-3&-1\end{matrix}\right).
\left(\begin{matrix}1&0\\0&1\end{matrix}\right)\left(\begin{matrix}x\\y\end{matrix}\right)=inverse(\left(\begin{matrix}1&-1\\-3&-1\end{matrix}\right))\left(\begin{matrix}3\\-37\end{matrix}\right)
The product of a matrix and its inverse is the identity matrix.
\left(\begin{matrix}x\\y\end{matrix}\right)=inverse(\left(\begin{matrix}1&-1\\-3&-1\end{matrix}\right))\left(\begin{matrix}3\\-37\end{matrix}\right)
Multiply the matrices on the left hand side of the equal sign.
\left(\begin{matrix}x\\y\end{matrix}\right)=\left(\begin{matrix}\frac{-1}{-1-\left(-\left(-3\right)\right)}&-\frac{-1}{-1-\left(-\left(-3\right)\right)}\\-\frac{-3}{-1-\left(-\left(-3\right)\right)}&\frac{1}{-1-\left(-\left(-3\right)\right)}\end{matrix}\right)\left(\begin{matrix}3\\-37\end{matrix}\right)
For the 2\times 2 matrix \left(\begin{matrix}a&b\\c&d\end{matrix}\right), the inverse matrix is \left(\begin{matrix}\frac{d}{ad-bc}&\frac{-b}{ad-bc}\\\frac{-c}{ad-bc}&\frac{a}{ad-bc}\end{matrix}\right), so the matrix equation can be rewritten as a matrix multiplication problem.
\left(\begin{matrix}x\\y\end{matrix}\right)=\left(\begin{matrix}\frac{1}{4}&-\frac{1}{4}\\-\frac{3}{4}&-\frac{1}{4}\end{matrix}\right)\left(\begin{matrix}3\\-37\end{matrix}\right)
Do the arithmetic.
\left(\begin{matrix}x\\y\end{matrix}\right)=\left(\begin{matrix}\frac{1}{4}\times 3-\frac{1}{4}\left(-37\right)\\-\frac{3}{4}\times 3-\frac{1}{4}\left(-37\right)\end{matrix}\right)
Multiply the matrices.
\left(\begin{matrix}x\\y\end{matrix}\right)=\left(\begin{matrix}10\\7\end{matrix}\right)
Do the arithmetic.
x=10,y=7
Extract the matrix elements x and y.
x-3-y=0
Consider the first equation. Subtract y from both sides.
x-y=3
Add 3 to both sides. Anything plus zero gives itself.
37-3x-y=0
Consider the second equation. Subtract y from both sides.
-3x-y=-37
Subtract 37 from both sides. Anything subtracted from zero gives its negation.
x-y=3,-3x-y=-37
In order to solve by elimination, coefficients of one of the variables must be the same in both equations so that the variable will cancel out when one equation is subtracted from the other.
x+3x-y+y=3+37
Subtract -3x-y=-37 from x-y=3 by subtracting like terms on each side of the equal sign.
x+3x=3+37
Add -y to y. Terms -y and y cancel out, leaving an equation with only one variable that can be solved.
4x=3+37
Add x to 3x.
4x=40
Add 3 to 37.
x=10
Divide both sides by 4.
-3\times 10-y=-37
Substitute 10 for x in -3x-y=-37. Because the resulting equation contains only one variable, you can solve for y directly.
-30-y=-37
Multiply -3 times 10.
-y=-7
Add 30 to both sides of the equation.
y=7
Divide both sides by -1.
x=10,y=7
The system is now solved.